Physiological and molecular regulatory mechanism of flavonoid metabolite biosynthesis during low temperature adaptation in Lavandula angustifolia Mill. - Pixiu Shi; Yinan Liu; Yu Wang; Ling Li; Yuchen Liang; Haijiao Lin; Zening Yuan; Guohua Ding (BMC Plant Biology)
Abstract Background Lavandula angustifolia Mill., a valuable aromatic plant, often encounters low temperature stress during its growth in Northeast China. Understanding the mechanisms behind its resistance to low temperatures is essential for enhancing this trait. Flavonoids play a vital role as stress-resistant compounds, significantly contributing to plants’ responses to low-temperature stress. However, the molecular mechanism governing flavonoid biosynthesis in L. angustifolia under low-temperature stress is remains inadequately understood. Results In this study, the physiological indexes, metabolome, and transcriptome of L. angustifolia were studied under temperatures of 30 °C, 20 °C, 10 °C, and 0 °C. The activities of peroxidase (POD) and superoxide dismutase (SOD) were notably the highest at 0 ℃, demonstrating optimal scavenging of reactive oxygen species (ROS). Among the 1150 metabolites analyzed, 52 flavonoid differential expression metabolites (DEMs) significantly increased at 10 °C and 0 °C. Furthermore, 55 differential expression genes (DEGs) involved in the flavonoid biosynthesis pathway showed significant up-regulation as the temperature dropped from 30 °C to 0 °C, indicating their role in positively regulating flavonoid biosynthesis under low temperatures. The flavonoid biosynthetic pathway was established based on key DEGs, including LaPAL-5, LaPAL-11, LaC4H-2, LaHCT, LaC3’H-4, LaCHS, LaF3PH-3, LaCCoAOMT-2, LaCCoAOMT-3, and LaDFR. Conserved domains predicted in 10 key proteins were identified as being responsible for catalytic functions that promote flavonoid biosynthesis under low temperatures. The synergistic enhancement between flavonoid DEMs and antioxidant enzymes was found to significantly contribute to the cold resistance of L.angustifolia. Conclusions The findings of this study provide a valuable reference for understanding the molecular regulation of L. angustifolia in response to low temperatures, laying a crucial foundation for future molecular breeding efforts aimed at developing cold-resistant varieties.